Rapid enzymatic burn debridement: A review of the paediatric clinical trial experience. Issue 5 (22nd May 2020) - Shoham, Yaron; Krieger, Yuval; Rubin, Guy; Koenigs, Ingo; Hartmann, Bernd; Sander, Frank; Schulz, Alexandra; David, Keren; Rosenberg, Lior; Silberstein, Eldad
Abstract: NexoBrid (NXB) has been proven to be an effective selective enzymatic debridement agent in adults. This manuscript presents the combined clinical trial experience with NXB in children. Hundred and ten children aged 0.5 to 18 years suffering from deep thermal burns of up to 67% total body surface area were treated with NXB in three clinical trials. Seventy‐seven children were treated with NXB in a phase I/II study, where 92.7% of the areas treated achieved complete eschar removal within 0.9 days from admission. Thirty‐three children (17 NXB, 16 standard of care [SOC]) participated in a phase III randomized controlled trial. All wounds treated with NXB achieved complete eschar removal. Time to complete eschar removal (from informed consent) was 0.9 days for NXB vs 6.5 days for SOC ( P < .001). The incidence of surgical excision was 7.9% for NXB vs 73.3% for SOC ( P < .001). Seventeen of these children participated in a phase III‐b follow‐up study (9 NXB and 8 SOC). The average long‐term modified Vancouver Scar Scale scores were 3.4 for NXB‐treated wounds vs 4.4 for SOC‐treated wounds (NS). There were no significant treatment‐related adverse events. Additional studies are needed to strengthen these results.